Chemically Fueled Self‐Assembly in Biology and Chemistry. (7th April 2021) - Das, Krishnendu; Gabrielli, Luca; Prins, Leonard J.
Abstract: Life is a non‐equilibrium state of matter maintained at the expense of energy. Nature uses predominantly chemical energy stored in thermodynamically activated, but kinetically stable, molecules. These high‐energy molecules are exploited for the synthesis of other biomolecules, for the activation of biological machinery such as pumps and motors, and for the maintenance of structural order. Knowledge of how chemical energy is transferred to biochemical processes is essential for the development of artificial systems with life‐like processes. Here, we discuss how chemical energy can be used to control the structural organization of organic molecules. Four different strategies have been identified according to a distinguishable physical‐organic basis. For each class, one example from biology and one from chemistry are discussed in detail to illustrate the practical implementation of each concept and the distinct opportunities they offer. Specific attention is paid to the discussion of chemically fueled non‐equilibrium self‐assembly. We discuss the meaning of non‐equilibrium self‐assembly, its kinetic origin, and strategies to develop synthetic non‐equilibrium systems. Abstract : Life is a non‐equilibrium state of matter maintained at the expense of energy. Nature uses chemical energy stored in molecules to sustain non‐equilibrium structures. This Review describes how chemical energy can be used to control the self‐assembly of organic molecules. The ability of chemists to implement the described strategies in a synthetic context will permit the development of artificial systems with life‐like properties.